Marine Ecology Geography - Fashchuk, Dmitry Ya (Springer, 2012)
This book's results in creation of the geographic-and ecologic model of marine basin as an information base for diagnosis of the marine ecosystem state, estimation of consequences of economic activity, and modelling of its changes with the use of mathematical tools.